Результаты исследования антропологического материала из некрополя Эски-Кермена - Радочин, В.Ю.; Бассалыго, О.А. (Материалы по археологии, истории и этнографии Таврии, 2006)
В 2003 году археологическая экспедиция Крымского отделения Института востоковедения под руководством А. И. Айбабина возобновила охранные раскопки на городище Эски-Кермен и его некрополей Раскопки на некрополе велись на участке с погребениями второй половины V1-XI вв. В результате проведенных работ было исследовано 17 погребальных сооружений (8 склепов и 9 грунтовых могил). Для обработки получен антропологический материал из 16 погребальных сооружений. In 2003 the archaeological expedition of the Crimean Branch of the Institute of Oriental Studies under the direction of Aibabin A. I. resumed the rescue excavations on Eski-Kermen site and its necropolis. The excavations on the necropolis took place on the part with burials dating to the second half of the 6*'' - 11'^ centuries. 17 burial constructions (8 vaults and 9 ditch graves) were investigated In the course of work. Anthropological material from 16 burial constructions was obtained for further research. Comparative characteristic of anthropological material obtained from the vaults and ditch graves became one of the directions of the undertaken work. On the whole craniological series were similar. Sex dimorphism is more distinctly traced on post-cranial skeletons from the vaults. The average age characteristics of the people buried in vaults was higher than of those buried in ditch graves. Pathological changes were similar for both compared groups, though there were some variation deviations. Some pathological changes on post-cranial skeletons buried in vaults and ditch graves enable to surmise a kind of activity of the people buried in the researched burials.